Does chili pepper consumption affect BMI and obesity risk? A cross-sectional analysis - Liu, Mengxue; Zhu, Yihao; Wang, Fei (Frontiers in Nutrition, 2024)
Background: The effects of chili intake on overweight and obesity have attracted significant interest in recent years. This study aimed to investigate the correlation between chili consumption frequency, body mass index (BMI), and obesity prevalence in the American population. Methods: Data from participants in NHANES (National Health and Nutrition Examination Survey) 2003-2006 were collected. We enrolled 6,138 participants with complete information on chili intake and BMI in this cross-sectional study. Multivariate logistic regression and sensitivity analyses were conducted to explore the relationship between chili intake frequency and BMI and obesity. Subgroup analyses and interaction tests were employed to assess the stability of the observed correlation. Results: Increased chili consumption frequency was linked to higher BMI values and a greater prevalence of obesity. Compared to the non-consumption group, the highest frequency group had a multivariate-adjusted β of 0.71 (95% CI: 0.05, 1.38) for BMI and an OR of 1.55 (95% CI: 1.22, 1.97) for obesity in the fully adjusted model. This positive association between chili intake frequency and obesity was more pronounced in females and older adults (≥ 60 years old). Conclusions: Our findings suggest a positive association between chili intake frequency and BMI and obesity in U.S. adults, suggesting that controlling chili intake frequency could potentially contribute to improved weight management in the general population.